Mathematical Quantification of Transmission in Experiments: FMDV Transmission in Pigs Can Be Blocked by Vaccination and Separation - Dekker, Aldo; van Roermund, Herman J. W.; Hagenaars, Thomas J.; Eblé, Phaedra L.; de Jong, Mart C. M. (Frontiers in Veterinary Science, 2020)
Quantitative understanding of transmission with and without control measures is important for the control of infectious diseases because it helps to determine which control measures (or combinations thereof) will be effective to reduce transmission. In this paper, the statistical methods used to estimate transmission parameters are explained. To show how these methods can be used we reviewed literature for papers describing foot-and-mouth disease virus (FMDV) transmission in pigs and we used the data to estimate transmission parameters. The analysis showed that FMDV transmits very well when pigs have direct contact. Transmission, however, is reduced when a physical barrier separates infected and susceptible non-vaccinated pigs. Vaccination of pigs can prevent infection by a single intradermal virus injection in the bulb of the heel, but it cannot prevent infection when directly exposed to either non-vaccinated or vaccinated FMDV infected pigs. Physical separation combined with vaccination can completely block transmission. Vaccination and separation can make a significant difference in the estimated number of new infections per day. The experimental transmission studies show that the combined effect of vaccination and physical separation can reduce transmission significantly (R<1), which is very relevant result for the control of between-farm transmission.